Evaluation of tbe Intensity Distribution by Image Processing - Mohammed, A.A.; Jabur, R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Image   processing   is  an   important   source   for   the  imageanalytical    in   order    to    get   variable    parameters    such   as   theintensity  .In  present   work  it  has  been  found   a  relation   between the  tensity and  number    of  pixd  in  the  image  ,  and  from  this relation   we  have   got   in  this  paper   the  intensity  di:s tribution   in the  photo  picture. One  of  the  an  important  sources   of  image  ist he  remote      sensing     technique.   The  development   relation   that we  have  got   is   a   numerical  analysis   added       to  the   remote sensing field .